Corticosteroid utilization patterns in a tertiary care teaching hospital, Rupandehi, Nepal - Mehta, Roshan Kumar; Aryal, Prakash; Chaudhary, Pankaj; Mehta, Vivek Kumar; Palikhey, Anjan; Chaudhary, Mukesh Kumar (Janaki Medical College Journal of Medical Science, 2026)
Background & Objectives: Corticosteroids are synthetic drugs that mimic the natural hormones produced by the adrenal cortex. Long-term or high-dose corticosteroid use is associated with significant adverse effects. Drug utilization research plays a critical role in monitoring and evaluating corticosteroid use and promote adherence to standard treatment guidelines. This study ais was to find out the utilization pattern of corticosteroids in outpatient settings Materials and Methods: A Prospective cross-sectional study was conducted to assess the prescription pattern of corticosteroid drugs in the outpatient department of Universal College of Medical Sciences. A total of 237 patients were included over a period of six months. Patients on any type of corticosteroid treatment were enrolled in the study and the prescribing as well as tapering patterns of steroids was reviewed. Results: Steroids were prescribed for various respiratory conditions 28.7%, dermatological conditions 28.7% and musculoskeletal disorders 22.4%. Budesonide was the most commonly prescribed drug, followed by prednisolone, deflazacort and methylprednisolone. The 39.53% of steroid drugs were administered through the oral route followed by inhalation 23.59% and topical route 22.92%. Among all steroid drugs, methylprednisolone was the most commonly tapered, followed by prednisolone and deflazacort. The combination of steroid drugs with other drugs accounted for 39%, among which formoterol and fusidic acid were found to be the most common. Conclusions: Findings indicate largely rational prescribing patterns; however, standardized guidelines and stricter regulatory enforcement are necessary to optimize corticosteroid use in Nepal. Involving clinical pharmacists can enhance therapy optimization, improve quality of life, and minimize adverse reactions and costs.